Efficacy and Safety of Hypofractionated Radiotherapy for the Treatment of Newly Diagnosed Glioblastoma Multiforme: A Systematic Review and Meta-Analysis - Liao, Guixiang; Zhao, Zhihong; Yang, Hongli; Li, Xianming (Frontiers in Oncology, 2019)
Background: Hypofractionated radiotherapy (HFR) is sometimes used in the treatment of glioblastoma multiforme (GBM). The efficacy and safety of HFR is still under investigation. The aim of this systematic review and meta-analysis was to provide a comprehensive summary of the efficacy and safety of HFR, and to compare the efficacy and safety of HFR and conventional fraction radiotherapy (CFR) for the treatment of patients with GBM, based on the results of randomized controlled trials (RCTs). Methods: A literature search was conducted to identify Phase II and III trials o comparing the efficacy and safety of HFR and CFR. Study selection, data extraction, and quality assessment, were conducted by two independent researchers. The analysis was performed using RevMan 5.3 and Stata 12.0. Results: Sixteen RCTs were included in the systematic review, and four RCTs were included in the meta-analysis. Participants treated with HRF and CRF had comparable overall survival (OS) (hazard ratio [HR]: 0.94, 95% confidence interval [CI]: 0.72–1.22, P=0.64) and progression-free survival (PFS) (HR: 1.09, 95% CI: 0.60–1.95, P=0.79), and similar rates of adverse events. However, in participants aged >70 years, those who received HFR had a higher OS than those who received CFR (HR: 0.59, 95% CI: 0.37–0.93, P=0.02). Conclusions: HRF is efficacious and safe for the treatment of GBM. In individuals aged >70 years, treatment with HRF is superior to CFR in terms of OS. The role of HFR in the treatment of GBM in younger individuals and those with good prognostic factors requires further research.